Does China-Pakistan Economic Corridor improve connectivity in Pakistan? A protocol assessing the planned transport network infrastructure. (April 2022) - Zhao, Jianting; Sun, Guibo; Webster, Chris
Abstract: China invested vastly in overseas infrastructure projects under the Belt and Road Initiative (BRI), which aims at improving international connectivity through collaboration with partner countries. For these countries, capturing the developments from BRI's massive transport infrastructure investments becomes a crucial economic multiplier. But there are few methods available in the existing literature. In this paper, we developed an analytical protocol that evaluates the changes in transport network connectivity before and after the BRI transport infrastructure construction, using open-source data and tools, and tested it on the China-Pakistan Economic Corridor (CPEC), the flagship project of BRI. Results show that China's transport infrastructure investment may improve connectivity and the potential for economic agglomeration in certain key cities and some regions in Pakistan but would widen the development inequality in the country. Our protocol benefits are threefold. First, it provides a quantitative estimation of the change in economic geography, accessibility and agglomeration-forming potentials, resulting from China's transport infrastructure investment. Second, it can be replicated to different scales and locations with easy-access open data. Last, its usage of open-source platforms and open data enables wide adoption by the public, especially agents with limited resources. Potential beneficiaries such as the governments of recipient countries, academics, funding providers, and private sectors can follow our protocol to assess the likely regional accessibility patterns and potential spatial economy from BRI-related transport infrastructure developments. Graphical abstract: Unlabelled Image Highlights: We devised a protocol to evaluate changes brought by CPEC transport infrastructure. CPEC may improve connectivity, integration and economy in key cities of Pakistan. We foresee an increased reliance on trains in post-CPEC with the upgraded railways. Remote regeions would merge better with the main transport network in post-CPEC. Transport investment may aggrevate development inequality between the east and west.